Opiate Concentrations in Hair from Subjects in a Controlled Heroin-Maintenance Program and from Opiate-Associated Fatalities - Musshoff, Frank; Lachenmeier, Katrin; Wollersen, Heike; Lichtermann, Dirk; Madea, Burkhard (Journal of analytical toxicology, 2005)
One month before (T-l) and 12 months after (T12) controlled intravenous administration of pharmaceutical heroin-HCI (10–1000 mg/d) in the context of a heroin-maintenance program, concentrations of opiates in head hair were determined (n = 46), using a validated gas chromatography-mass spectrometry method with limits of detection (LOD) between 0.02 and 0.04 ng/mg. In addition, a collective of opiate-associated fatalities was examined (n = 24). The obtained concentrations in the proximal segment (1 cm) of the patients were between 0.04 and 1.16 ng/mg (mean 0.13 ng/mg) for heroin (HER), between 0.02 and 32.41 ng/mg (mean 1.48 ng/mg) for 6-monoacetylmorphine (MAM) and between 0.03 and 11.79 ng/mg (mean 1.19 ng/mg) for morphine (MOR). With the exception of the analyte HER, there was no other statistically significant difference in the concentrations in comparison to the opiate fatalities [HER 1.55–5.20 ng/mg mean 3.38 ng/mg), MAM 0.04–30.01 rig/rag (mean 2.14 rig/rag), and MOR 0.03–11.87 ng/mg (mean 1.15 ng/mg) in the proximal segments]. After controlled HER administration, a correlation between the dose and the total opiate concentration in the hair was found (r = 0.66). These results disagree with the observations of authors who found only limited dose-concentration relationships after heroin abuse in hair. When considering a single analyte, the coefficient of correlation increased in correspondence to the respective plasma half-life (r = 0.42, r = 0.58, and r = 0.69 for HER, MAM, and MOR). The latter findings are in agreement with the report that states that this correlation is influenced by the plasma half-lifes of analytes. Codeine and acetylcodeine (AC) were detected in 50% and 43.5% (T-1) and 13% and 10.9% (T12) of the samples of the HER-maintenance program, as well as in 33.3% and 16.7% in opiateassociated fatalities, respectively. The lack of differences between obtained opiate concentrations in the hair of participants in a controlled heroin maintenance program and of opiate-associated fatalities does not support the hypothesis that an absence of tolerance can be regarded as a potential cause of death. In addition, the lack of AC, which was also observed in the majority of the deaths, questions its applicability as a characteristic marker of the consumption of illicit heroin.